PWE-052 Bowelscope Screening – The South Of Tyne And Wear Experience. (9th June 2014) - Bevan, R; Miller, H; Thapa, D; Ritchie, M; Painter, J; Rees, C
Abstract : Introduction: The National Bowel Cancer Screening Programme has been extended to include a one-off flexible sigmoidoscopy (FSIG) to all aged 55, after a large UK study demonstrated reduction in colorectal cancer incidence and death rates when FSIG is performed and adenomas removed. BowelScope screening is being piloted in 6 centres – South of Tyne and Wear (SOTW), Norwich, St Mark's, Surrey, Kent and Medway, and Wolverhampton. SOTW was the first centre to offer screening. Methods: We describe delivery of BowelScope at SOTW. The Bowel Cancer Screening System (BCSS) database was interrogated for procedural data. A study was performed recording timings of lists. Patients complete a satisfaction survey the morning after the procedure; anonymised results are provided to the centre. Results: 2 endoscopists were accredited in March 2013– 1 medical research fellow, and 1 staff grade surgeon. 2 existing BCSP colonoscopists also support the BowelScope lists as required. First invitations were sent from the Northern Hub on 21.03.13, and first screening list held on 07.05.13. Lists are held on Tuesday and Thursday evenings, recently increasing to include Saturday lists. Lists initially had 12 slots available, but were reduced to 10 in light of over-running lists. Average list length 229 min (11/12 points) vs 199 min (≤10 points). 248 FSIGs were completed in ≤110 min, 172 in 11–15 min, and 88 in > 115 min (data missing in 7). Comfort was recorded by SSPs as none/minimal/mild discomfort in 484 cases, and moderate/severe in 35. Entonox was used by 94 screenees. Patient surveys showed patient reported moderate/severe pain in 44%. Failure to attend– 52 (9%). As of 20.12.2013: Conclusion: We demonstrate that BowelScope screening can be adequately delivered by existing screening centres. Adjustments may need to be made to list templates in order to ensure minimal waiting for patients. Uptake is less than for the FOB programme but is higher than in early pilots. Some slots are wasted with the 9% FTA rate; a new text messaging reminder service has been developed to address this. Patient reported pain levels are higher than those recorded by the SSPs, highlighting a need for accurate assessment of patient experience. Disclosure of Interest: None Declared.